Time Course of Severe Fever With Thrombocytopenia Syndrome Virus and Antibodies in Patients by Long-Term Follow-Up Study, China - Hu, Lifen; Kong, Qinxiang; Liu, Yanyan; Li, Jiajia; Bian, Tingting; Ma, Xuejiao; Ye, Ying; Li, Jiabin (Frontiers in Microbiology, 2021)
Objectives: The objective was to describe the changes of severe fever with thrombocytopenia syndrome virus (SFTSV) and antibody in the disease course and explore the relationship between antibody titer levels and patients' prognosis. Methods: The levels of SFTSV, virus-specific IgM, and IgG titers in 54 SFTS patients were measured dynamically by real-time PCR and ELISA by nine years’ follow-up, respectively. The correlation analysis of antibody titers with individual serum cytokines was calculated using the Spearman test. Results: The serum SFTSV virus turned negative as early as on the 10th day from the onset in the patient, the average time was 22.45 ± 7.6 days. SFTSV-specific IgM turned positive as early as the 3rd day from the onset, increased gradually within the first 2 months, decreased gradually three months later, and disappeared after six months in all the patients. The SFTS patients have SFTSV-specific IgG antibodies at the average time of 17 days from onset, the time was later in severely ill patients than in mild patients (23 ± 1.4 vs 14.3 ± 1.0, P < 0.0001). The IgG titers remained at the peak levels during the periods from 6 months to 1 year and decreased from the second year gradually. Severe patients had the highest IgG levels than mild patients and also had a slower decreasing trend. During follow-up, only one lost IgG antibody seven years later, no chronic infection and sequela were found among the 54 patients. All the patients didn't have SFTSV reinfection even if they were bitten by ticks again. The correlation analysis showed a positive relationship between inflammatory factors and IgG antibody levels. Conclusions: IgM antibody has important value in early diagnose of SFTS as SFTSV. Adaptive immune response contributes to long-lasting IgG antibodies. SFTS survivors have persistent immunity to SFTSV after infection.